Бухгалтерский учет - Козлова Е. П. Елизавета Петровна; Парашутин Н. В. Николай Васильевич; Бабченко Т. Н. Татьяна Николаевна; Галанина Е. Н. Елена Николаевна (Москва, Финансы и статистика, 1996)
Исключено из фонда НТБ ТПУ